Arbitraje limitado bajo fondeo basado en desempeño (2016)
In scenarios of increasing pessimism, arbitrageurs affect processes by inducing a recuperation in demand for a risky asset (demand effect) or as a result of their capacity to transfer resources to scenarios of scarce liquidity (the liquidity effect). If the liquidity effect is active, arbitrageurs respond to waves of pessimism and, as a consequence, increase their short positions or reduce the amount invested in the risky asset today. In this manner, they allow the price to fall in the present, thereby stabilizing losses if pessimism sharpens in the future. The liquidity effect is smaller when investors are risk-averse or when there are short-term restrictions on sales, a situation that translates into volatility in future prices.